A pilot study investigating whether focusing on body functionality can protect women from the potential negative effects of viewing thin-ideal media images. (June 2016) - Alleva, Jessica M.; Veldhuis, Jolanda; Martijn, Carolien
Highlights: We explored if focusing on body functionality buffers effects of thin-ideal images. Participants did a functionality or control task before viewing thin-ideal images. Participants focusing on functionality reported higher functionality satisfaction. Participants focusing on functionality also felt greater body appreciation. Focusing on functionality could protect women from effects of thin-ideal imagery. Abstract: This pilot study explored whether focusing on body functionality (i.e., everything the body can do ) can protect women from potential harmful effects of exposure to thin-ideal images. Seventy women ( M age  = 20.61) completed an assignment wherein they either described the functionality of their body or the routes that they often travel (control). Afterward, participants were exposed to a series of thin-ideal images. Appearance and functionality satisfaction were measured before the assignment; appearance and functionality satisfaction, self-objectification, and body appreciation were measured after exposure. Results showed that participants who focused on body functionality experienced greater functionality satisfaction and body appreciation compared to control participants. Therefore, focusing on body functionality could be a beneficial individual-level technique that women can use to protect and promote a positive body image in the face of thin-ideal images. Research including a condition wherein participants are exposed to (product-only) control images is necessary to draw firmer conclusions.